2015
DOI: 10.1007/s40870-015-0014-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Dynamic Properties of Al 5456 FSW Welds Using the Virtual Fields Method

Abstract: The present study focuses on the identication of the evolution of the dynamic elasto-plastic properties of Al 5456 FSW welds. An innovative method is proposed to make best use of the data collected with full-eld measurements during dynamic experiments, and achieve identication of the mechanical properties of heterogeneous materials without requiring measurement of the load. Compressive specimens have been submitted to high strain-rate loading through a Split Hopkinson Pressure Bar (SHPB) device while displacem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 53 publications
(64 reference statements)
0
18
0
Order By: Relevance
“…In recent years, digital image correlation (DIC), a powerful and versatile optical technique for non‐contact, full‐field deformation measurement, has been widely accepted and used as an alternative deformation measurement technique for VFM identification. Based on the full‐field measurements provided by DIC, VFM has been successfully used for the characterisation of materials with various constitutive relations, such as metals under different temperatures and different strain rates, polymeric foams, composites, biological materials, and wood …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, digital image correlation (DIC), a powerful and versatile optical technique for non‐contact, full‐field deformation measurement, has been widely accepted and used as an alternative deformation measurement technique for VFM identification. Based on the full‐field measurements provided by DIC, VFM has been successfully used for the characterisation of materials with various constitutive relations, such as metals under different temperatures and different strain rates, polymeric foams, composites, biological materials, and wood …”
Section: Introductionmentioning
confidence: 99%
“…As the input data of VFM identification, the quality of measured deformation fields plays a vital role in VFM. In previous studies regarding DIC‐based VFM, 2D‐DIC has been usually employed to measure the deformation fields . However, various works demonstrated that 2D‐DIC with a regular lens cannot deliver accurate results due to the unavoidable out‐of‐plane movements of the specimen.…”
Section: Introductionmentioning
confidence: 99%
“…The group then extended their work with a simulation to inspect a wood beam for defects . Several researchers combined global and local VFM procedures to locate impact damage in composite plates and regions near weld zones . Segmented VFM was used by Hagman et al on a different paperboard material to identify stiffness in discrete regions and by Kretschmann et al in wood stiffness identification.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Several researchers [6][7][8] combined global and local VFM procedures to locate impact damage in composite plates and regions near weld zones. [9][10][11] Segmented VFM was used by Hagman et al [12] on a different paperboard material to identify stiffness in discrete regions and by Kretschmann et al [13] in wood stiffness identification. Results of a numerical simulation of a solid rocket propellant with smoothly varying modulus have been examined using VFM, leading to a polynomial approximation for modulus.…”
mentioning
confidence: 99%
“…However, it is possible to extend this approach to transient waves by deriving the acceleration through double temporal differentiation. This was adopted in several papers on composites , concrete and welds . Recently, a very interesting article was published in Strain where a sawbone specimen was submitted to longitudinal vibrational excitation in the ultrasonic range, and its response measured by digital image correlation (DIC).…”
Section: Introductionmentioning
confidence: 99%